Software Technologies : 9th International Joint Conference, ICSOFT 2014, Vienna, Austria, August 29-31, 2014, revised selected papers /: 9th International Joint Conference, ICSOFT 2014, Vienna, Austria, August 29-31, 2014, revised selected papers. (2015) - Unknown
No abstract available